Escuela nueva modos de reproducción monoculturales, desde el racismo cognitivo frente a una educación intercultural (2016)
The analysis of rural education in Colombia, Model-centric new school, It highlights the irrelevance and incoherence of this, against a contextualized education, that meets the needs of children in each region; This evidence the claims, from the state, It operates as an ideological device replicating from school a massive model that colonizes; from practices, speeches, school governance, generating a type of social relations within this, obscuring the subject and affirming from universalizations and generalizations where every child to a single student are reduced (there is only one type of farm boy), emerging as practiced cognitive racism, that they show a hierarchical structure, asymmetric, racist and laminating. The new school model generates an instrumental methodological framework that addresses a type subject to a society with specific needs. This work was conducted in three rural schools of Quindío doing an analysis of the master module and tutorials, surveys of teachers and students and reviewing the test results to know a year in fifth grade. It is concluded that new school does not take into account the worldview of rural children and their relationship with the world in which they represent, It is becoming apparent asymmetry from culture since the new school model does not recognize any intercultural condition in rural children in Colombia's educational context.